An pagbalhin ha tagpuro - Ramos, Firie Jill T.; Gaspay, Jodalyde G. (Tacloban City : Leyte Normal University, 2015)
Written in the context of post Yolanda. This storybook carries a message of hope and rebuilding, in the light of the disaster that visited the region.
In Waray and English.
Keywords: Children's stories, Waray; Electronic Books